Medición y evaluación en comunicación estratégica. Caso de estudio Oliojoya Industria Aceitera Cía. Ltda. - Guerrero Menéndez, Karina Mercedes (2014)
No matter the size of the business, organizations need structured organizational communication, instructional communication skills, leadership, teamwork to be directed to the improvement in production processes and achieve excellent results. Every company must have a communications department or a specialist to apply the strategies of communication, their work will diagnose, evaluate public relations so as to have links with the mission and goals of the organization. Within organizations use communications is vital, makes it possible to achieve the objectives, promotes positive attitudes to the essential internal and external stakeholders for the existence and progress of the same. Because the source of problems in organizations and daily life are linked to the lack of conversation and not be able to relate to each other.